Gemeinsam gegen Deutschland : Warschaus jiddische Presse im Kampf gegen den Nationalsozialismus (1930–1941) - Klotz, Anne-Christin (Europäisch-jüdische Studien – Beiträge, 2022)
By analyzing Warsaw’s Yiddish daily press, this volume reveals how Polish Jews gained and disseminated subversive knowledge of National Socialist Germany in spite of censorship and repression, and also initiated campaigns of protest and solidarity to the benefit of the people being persecuted there